Strategy for the Evaluation, Diagnosis, and Support of Children And Adolescents with Intellectual Disabilities in Colón, Panama (Global Journal of Human-Social Science, 2024)
The evaluation and diagnosis of a person with intellectual disability implies establishing the existence of significantly limiting indicators both in intellectual functions and adaptive behaviors in different contexts of daily life. This article aims to identify the strengths and weaknesses of people with intellectual disabilities, in order to propose an evaluation and diagnosis strategy not only to obtain a characteristic or classification, but also aimed at improving the programs and support services of people with intellectual disabilities at the institutional level. This study was conducted in the city of Colón, Panama. Through a non-experimental design, with a single group, quantitative, qualitative-explanatory longitudinal; of the 51 children and adolescents with intellectual disabilities from the Panamanian Institute of Special Education of Colón. Each child and adolescent were evaluated through the Adaptive Behavior Assessment System test (ABAS-II 2013). The analyzed findings of the results of the evaluation and diagnoses of the study revealed the importance of optimizing and strengthening the support systems of people with intellectual disabilities focused on an inclusive environment interrelated with the community, school, family, and society.
Keywords: evaluation; diagnosis; intellectual disability; adaptive skill; support